Cytotoxicity of titania nanoparticles towards waste water isolate Exiguobacterium acetylicum under UVA, visible light and dark conditions. Issue 3 (September 2015) - Mathur, Ankita; Raghavan, Archanaa; Chaudhury, Pallavi; Johnson, J.B.; Roy, Rajdeep; Kumari, Jyoti; Chaudhuri, Gouri; Chandrasekaran, N.; Suraishkumar, G.K.; Mukherjee, Amitava
Graphical abstract